DISTRIBUTION OF SPOT URINARY ELECTROLYTES AND THEIR PREDICTED 24 HOUR LEVELS BY ETHNICITY ASSOCIATIONS WITH MORTALITY IN A LONGITUDNAL COHORT. (April 2021) - Saluja, Sushant; Powell, Leo -Paul; Jiang, Xiao; Heald, Adrian; Cruickshank, Kennedy; Anderson, Simon
Abstract : Objective: Hypertension is a modifiable risk factor for development of cardiovascular disease. Increased urinary sodium excretion, representing high dietary sodium intake is associated with hypertension. Observational cohort studies consistently demonstrate a low sodium intake is also associated with increased mortality. It is not known what the optimal amount of salt intake is good for cardiovascular health. Hypertension is a modifiable risk factor for development of cardiovascular disease. Increased urinary sodium excretion, representing high dietary sodium intake is associated with hypertension. Observational cohort studies consistently demonstrate a low sodium intake is also associated with increased mortality. It is not known what the optimal amount of salt intake is good for cardiovascular health. Design and method: Urine samples were obtained from 331 people [100 Afro-Caribbean (AC), 118 European and 113 Gujarati Indians] to estimate 24-hour sodium and potassium excretion. Association between estimated urinary sodium, potassium and creatinine excretion to composite outcome of major cardiovascular event and death were examined. We also aimed to study if ethnicity influenced this relationship. Results: We noted heterogeneity in association between sodium, potassium, creatinine excretion and mortality. Significantly higher, age-sex adjusted, spot urinary sodium (OR- 2.7; CI – 1.9–3.2) and creatinine (OR- 1.7; CI – 1.2–2.2) levels were seen in AC men who also had higher mean diastolic blood pressure (84 ± 5.5 vs 78 ± 3.3; p < 0.05). Overall, 42.9% (n = 142) of the cohort were hypertensive. Of the 331 eligible participants at baseline, a total 69 cardiovascular deaths were recorded. Spot sodium levels were higher in those who died from cardiovascular causes [(125.3; CI- 116.9, 133.7) mmol/l] vs [(108.7; CI - 99.4 – 118.0); p = 0.02]. Survival was associated with a urinary sodium below and urinary potassium above the median. There was no survival advantage associated with differences in creatinine output. Conclusions: This study estimates a sodium intake of between 2.0 g/day and 2.5 g/day as being associated with a lower risk of death and cardiovascular events. A higher potassium excretion was associated with a lower risk of death and cardiovascular events. Creatinine output made no difference to survival advantage.